2010
DOI: 10.1177/0165025409351386
|View full text |Cite
|
Sign up to set email alerts
|

Differences in causal estimates from longitudinal analyses of residualized versus simple gain scores: Contrasting controls for selection and regression artifacts

Abstract: This study estimates the causal effects of six corrective actions for children's problem behaviors, comparing four types of longitudinal analyses that correct for pre-existing differences in a cohort of 1,464 4- and 5-year-olds from Canadian National Longitudinal Survey of Children and Youth (NLSCY) data. Analyses of residualized gain scores found apparently detrimental effects of all corrective actions by parents and professionals on subsequent antisocial behavior and hyperactivity. In contrast, analyses of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 20 publications
2
41
0
Order By: Relevance
“…Moreover, the non-significant associations generally reversed signs when predicting simple gain scores in the latent variable of externalizing behavior problems, consistent with small residual selection biases[44,48,56]. These results suggest that the findings of all three types of analyses are due to residual selection biases that are minimized by controlling for a latent variable for externalizing behavior problems to reduce measurement error and to maximize the comprehensiveness of the proxy for the selection process.…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, the non-significant associations generally reversed signs when predicting simple gain scores in the latent variable of externalizing behavior problems, consistent with small residual selection biases[44,48,56]. These results suggest that the findings of all three types of analyses are due to residual selection biases that are minimized by controlling for a latent variable for externalizing behavior problems to reduce measurement error and to maximize the comprehensiveness of the proxy for the selection process.…”
Section: Discussionsupporting
confidence: 54%
“…No disciplinary tactic was ever associated with reduced child behavior problems, and 7 of the 12 tactics predicted significantly worse behavior problems in at least one analysis. Moreover, two of those studies found that two corrective actions by professionals, psychotherapy and Ritalin, both looked as harmful as spanking when analyzed in the same way (see Table 1; Larzelere, Cox, & Smith, 2010;Larzelere, Ferrer, Kuhn, & Danelia, 2010). Gershoff et al (2010).…”
Section: Recent Evidence Against All Corrective Actionsmentioning
confidence: 99%
“…This finding has been replicated at least eight times, yielding a small but significant mean of β = 0.07 with antisocial types of behavior problems in a recent meta-analysis (Ferguson, 2013). Two of those replications found similar adverse effects for nonphysical punishments, psychotherapy, and Ritalin on antisocial behavior or hyperactivity when controlling for initial differences on those outcomes (Larzelere, Cox, & Smith, 2010;Larzelere, Ferrer, et al, 2010). In the first major evaluation of Head Start, Cicirelli (1969) also found adverse effects on subsequent academic success even after using a matched comparison group and controlling statistically for socioeconomic status.…”
Section: Purported Cause Versus Systematic Biasesmentioning
confidence: 75%
“…Second, this pattern of contradictory effects for ANCOVA-type analyses in comparison with analyses of simple change scores has been shown for other corrective actions, including out-ofhome placements (Berger, Bruch, Johnson, James, & Rubin, 2009) and job-training programs (LaLonde, 1986). Third, one study showed that this same pattern of contradictory results replicates after reversing the waves of data (Larzelere, Ferrer, et al, 2010)-an old strategy for discriminating between true causal effects and statistical artifacts (Galton, 1886). These examples illustrate the importance of checking the robustness of findings across alternative statistical analyses, which is a practice much more typical of economics than of developmental psychology (Duncan, Engel, Claessens, & Dowsett, 2014).…”
Section: Improved Controls For Biasesmentioning
confidence: 87%
See 1 more Smart Citation